Characterization of human epithelial resident memory regulatory T cells - Sato, Takuya; Ogawa, Youichi; Yokoi, Kazunori; Nagasaka, Yuka; Ishikawa, Aoha; Shiokawa, Ichiro; Kinoshita, Manao; Watanabe, Rei; Shimada, Shinji; Tanaka, Atsushi; Momosawa, Akira; Kawamura, Tatsuyoshi (Frontiers in Immunology, 2022)
Human resident memory regulatory T cells (Tregs) exist in the normal, noninflamed skin. Except one, all previous studies analyzed skin Tregs using full-thickness human skin. Considering that thick dermis contains more Tregs than thin epidermis, the current understanding of skin Tregs might be biased toward dermal Tregs. Therefore, we sought to determine the phenotype and function of human epidermal and epithelial Tregs. Human epidermis and epithelium were allowed to float on a medium without adding any exogenous cytokines and stimulations for two days and then emigrants from the explants were analyzed. Foxp3 was selectively expressed in CD4+CD103− T cells in the various human epithelia, as it is highly demethylated. CD4+CD103−Foxp3+ cells suppressed proliferation of other resident memory T cells. The generation and maintenance of epithelial Tregs were independent of hair density and Langerhans cells. Collectively, immune-suppressive CD4+CD103−Foxp3+ Tregs are present in the normal, noninflamed human epidermis and mucosal epithelia.